PENGARUH LITERASI KEWIRAUSAHAAN, LITERASI KEUANGAN, DAN MEDIA SOSIAL TERHADAP MOTIVASI BERWIRAUSAHA MELALUI MINAT BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS PGRI WIRANEGARA - Romadloniah, Mutiara; Pradikto, Sugeng; Suchaina, Suchaina (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
Entrepreneurship is the key to creating innovation and jobs that can encourage country's economic growth. where every period the unemployment rate increases. Therefore, to reduce the unemployment rate with entrepreneurial activities, the difficulty that many find is growing motivation and interest in entrepreneurship in students. This research aims to determine the influence of entrepreneurial literacy, financial literacy, social media on entrepreneurial motivation mediated by entrepreneurial interest. This research includes a quantitative approach, the population of this research is 186 economic education students for the 2021-2023 class. The research sample was 65 respondents. The instrument used was a questionnaire consisting of 25 statements. The analytical tests used are the classical assumption test, path analysis test, and hypothesis test. The results of this research are: 1) there is a direct influence between the variables Entrepreneurship Literacy, Financial Literacy, and social media on entrepreneurial motivation. 2) there is a direct influence between the variables Entrepreneurship Literacy, Financial Literacy, and social media on motivation for entrepreneurship. 3) there is an indirect influence between the variables Entrepreneurship Literacy, Financial Literacy, and social media on motivation for entrepreneurship through interest in entrepreneurship.